Rapid Response and Slow Recovery of the H3K4me3 Epigenomic Marker in the Liver after Light-mediated Phase Advances of the Circadian Clock. Issue 4 (August 2018) - Grygoryev, Dmytro; Rountree, Michael R.; Rwatambuga, Furaha; Ohlrich, Anna; Kukino, Ayaka; Butler, Matthew P.; Allen, Charles N.; Turker, Mitchell S.
Mammalian tissues display circadian rhythms in transcription, translation, and histone modifications. Here we asked how an advance of the light-dark cycle alters daily rhythms in the liver epigenome at the H3K4me3 (trimethylation of lysine 4 on histone 3) modification, which is found at active and poised gene promoters. H3K4me3 levels were first measured at 4 time points (zeitgeber time [ZT] 3, 8, 15, and 20) during a normal 12L:12D light-dark cycle. Peak levels were observed during the early dark phase at ZT15 and dropped to low levels around lights-on (ZT0) between ZT20 and ZT3. A 6-h phase advance at ZT18 (new lights-on after only 6 h of darkness) led to a transient extension of peak H3K4me3 levels. Although locomotor activity reentrained within a week after the phase advance, H3K4me3 rhythms failed to do so, with peak levels remaining in the light phase at the 1-week recovery time point. Eight weekly phase advances, with 1-week recovery times between each phase advance, further disrupted the H3K4me3 rhythms. Finally, we used the mPer2 Luc knockin mouse to determine whether the phase advance also disrupted Per2 protein expression. Similar to the results from the histone work, we found both a rapid response to the phase advance and a delayed recovery, the latter in sync with H3K4me3 levels. A model to explain these results is offered.